PENGARUH PENJUALAN DAN BEBAN POKOK PENJUALAN TERHADAP LABA BERSIH PADA PERUSAHAAN MANUFAKTUR SUB SEKTOR OTOMOTIF DAN KOMPONEN YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PERIODE 2021-2024 - MUHAMMAD RIZAL SATRIA; Fanya Harum Amaliani (Universitas Logistik dan Bisnis Internasional, 2026)
A company's ability to sustain its operations in a dynamic business environment heavily depends on its financial performance, one of which can be measured through net profit. This reseacrh seeks to examine the impact of sales and cost of goods sold on net profit among manufacturing firms in the automotive and components sub-sector listed on the Indonesia Stock Exchange. The study applies a quantitative approach with a causal-associative method. The data employed consist of secondary financial reports from the 2021–2024 period, which were obtained from the official IDX website at www.idx.co.id. The analytical tools utilized include Pearson product-moment correlation, multiple correlation, multiple linear regression, coefficient of determination, t-test, and F-test, processed with the assistance of SPSS software. The findings reveal that sales have a significant positive effect on net profit, showing a very strong correlation between the two variables. Conversely, cost of goods sold exerts a significant negative effect on net profit, also with a very strong correlation. Moreover, sales and cost of goods sold collectively influence net profit, with a strong simultaneous relationship between both independent variables and net profit.